We like to move it, move it: A perspective on performing passive leg movement as a non-invasive assessment of vascular function in pediatric populations - D’Agata, Michele N.; Matias, Alexs A.; Witman, Melissa A. (Frontiers in Physiology, 2023)
The passive leg movement (PLM) technique is a noninvasive assessment of lower-limb vascular function. PLM is methodologically simple to perform and utilizes Doppler ultrasound to determine leg blood flow (LBF) through the common femoral artery at rest and in response to passive movement of the lower leg. LBF responses to PLM have been reported to be mostly nitric oxide (NO)-mediated when performed in young adults. Moreover, PLM-induced LBF responses, as well as the NO contribution to PLM-induced LBF responses, are reduced with age and in various diseased populations, demonstrating the clinical utility of this noninvasive test. However, no PLM studies to date have included children or adolescents. Since its conception in 2015, our laboratory has performed PLM on hundreds of individuals including a large cohort of children and adolescents. Thus, the purpose of this perspective article is threefold: 1) to uniquely discuss the feasibility of performing PLM in children and adolescents, 2) to report PLM-induced LBF values from our laboratory in 7-17-year-olds, and 3) to discuss considerations for making comparisons among pediatric populations. Based on our experiences performing PLM in children and adolescents (among various other age groups), it is our perspective that PLM can feasibly be performed in this population. Further, data from our laboratory may be used to provide context for typical PLM-induced LBF values that could be observed in children and adolescents, as well as across the lifespan.